Leaf damage data on European beech leaves from saplings and mature trees from Lower Saxony, Germany in 2019 - Dragan Matevski; Jonas Glatthorn; Estela C Foltran (PANGAEA, 2022)
Leaf damage data on European beech leaves from saplings and mature trees from Lower Saxony, Germany. Three forest stand types were studied (European beech/Douglas fir mixture, European beech monoculture, and European beech/Norway spruce mixture) at six different sites, three in southern (site 1-3) and three (4-6) in northern Lower Saxony, Germany. At each plot 20 leaves from 20 saplings and 80 leaves from 5 mature trees were sampled in August 2019. After sampling the dorsal side of leaves was scanned and the amount of damage was estimated with an image processing software called ImageJ. Damage is distinguished into total, pathogen and herbivory damage which is further distinguished into chewing, sucking, mining, skeletonizing and gall damage.